Structure Determination of Pentacyclic Pyridoacridine Alkaloids from the Australian Marine Organisms Ancorina geodides and Cnemidocarpa stolonifera. Issue 22 (23rd June 2014) - Tran, Trong D.; Pham, Ngoc B.; Quinn, Ronald J.
Abstract: Chemical investigation of two marine samples A. geodides and C. stolonifera led to the isolation of six pentacyclic pyridoacridine alkaloids, in which two compounds, ancorine A and cnemidine A, are new pyridoacridines. Their structures were determined by NMR spectroscopic analysis supported by quantum mechanical calculations of 13 C NMR chemical shifts. This is the first study demonstrating that the pyridoacridine structure class can be assigned on the basis of quantum mechanical calculations. The isolated pyridoacridine alkaloids showed selective cytotoxicity against human prostate cancer cells (PC3) compared with human neonatal foreskin fibroblast noncancer cells (NFF). Abstract : Quantum mechanical calculations together with statistical methods allowed the assignment of two new pentacyclic pyridoacridine alkaloids, ancorine A and cnemidine A. Cytotoxicity of the isolated compounds against PC3 prostate cancer cell line PC3 is reported.